2003
DOI: 10.1067/mhn.2003.51
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Normative Cochlear and Vestibular Measurements to Aid in the Diagnosis of Inner Ear Malformations

Abstract: Routine measurement of the cochlear height and bony island of the lateral semicircular canal, in conjunction with visual inspection of CT images, will increase recognition of common inner ear malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 7 publications
4
112
2
2
Order By: Relevance
“…2 and are taken from Purcell et al (2003) and Seibel et al (2006). The middle ear impedance, ZME, is the impedance seen from inside the inner ear at the OW.…”
Section: Contribution From the Inner Earmentioning
confidence: 99%
“…2 and are taken from Purcell et al (2003) and Seibel et al (2006). The middle ear impedance, ZME, is the impedance seen from inside the inner ear at the OW.…”
Section: Contribution From the Inner Earmentioning
confidence: 99%
“…Unlike most anatomic structures, the inner ear labyrinth does not change in size after birth. 18 Therefore, the establishment of normative data for the dimensions of the inner ear structures by using CT imaging will allow consistent and accurate assessment for patients of all ages. Purcell et al 18,19 demonstrated that standardized measurements of inner ear structures on temporal bone CT scans can complement visual analyses and greatly aid the identification of inner ear malformations.…”
Section: Discussionmentioning
confidence: 99%
“…18 Therefore, the establishment of normative data for the dimensions of the inner ear structures by using CT imaging will allow consistent and accurate assessment for patients of all ages. Purcell et al 18,19 demonstrated that standardized measurements of inner ear structures on temporal bone CT scans can complement visual analyses and greatly aid the identification of inner ear malformations. On the basis of this premise, our prospective evaluation identified 7 different inner ear abnormalities that were statistically significant between individuals with Cornelia de Lange syndrome and those with normal hearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A. For the dimensions of the model the vestibule was assumed to be of 6 mm height while the scala vestibuli and scala tympani were 2 mm [8]. The BC motion was assumed to be a longitudinal wave in the petrous part of the temporal bone [11].…”
Section: Model Of Cochlear Motion During Bc Stimulationmentioning
confidence: 99%